MEDICO-LEGAL STUDY OF NON-FATAL ROAD TRAFFIC INJURIES (Iraqi Journal of Medical Sciences, 2016)
Background:Road traffic accidents are global problems, which represent one of the major causes of disability and death worldwide leading to unpleasant results on individuals, their families and their society.Objective:To study the incidence of road traffic accidents in relation to socio-demographic factors, and to find out the patterns and distribution of the resulting injuries.Method:This study included (375) victims of road traffic accidents whom were brought to the casualty room in AL-Gamhoria Teaching Hospital in Aden-Yemen for medical and legal evaluation during the period from 1st January up to 31 December 2010. Information collected consisted of personal identification data, and accident characteristics that were obtained from patients, close relatives, and other available persons who were present at the time of incidence.Results:Only 140 (37.4%) of victims were hospitalized. 32% of road traffic accidents (RTAs) was observed among those aged 21-30 years with predominance of male (82.9%). The illiterates were the victims in 38.7%, students (48%), and single (60%). Most of cases from middle and lower socio-economic classes (53.3% and 40%, respectively). Pedestrians (38.5%) and passengers (35.7%) were the victims in most of cases. Light motor vehicle was involved in 61.5%. Sideway and hit and run were the most common types of collisions seen in (33.3% and 30.2%, of all cases respectively). Most of the accidents occurred between 12.01pm to 06.00pm. Most of the accidents occurred during summer season, mainly in the weekend. Multiple superficial injuries like abrasions, contusions, and lacerations wee the commonest pattern of injuries. Limb injuries were the most (46.5%) followed by the head (26.4%). Conclusion:The middle aged group males were more common involved in road accidents. The pedestrians were mostly affected. The Injuries were mostly caused by light motor vehicles than other vehicles. Accidents were more common in the summer season and during weekend, in afternoon hours. Multiple superficial injuries were the commonest injury, and the head and limbs were the most common site of injuries among victims of non-fatal road traffic accidents.Key words:Non-fatal, road traffic accidents, injury patterns and distribution.
Keywords: Nonfatal; road traffic accidents; injury patterns and distribution